TAXING THE DIGITAL INDUSTRY: NAVIGATING THE NEW LEGAL AND POLICY LANDSCAPE - Loso Judijanto; Rita Hayati; Iyad Abdallah Al- Shreifeen; Hadenan Towpek (Adisam Publisher, 2026)
The digital industry, which is often not bound by geographical boundaries, presents great challenges to the traditional taxation system, especially in terms of determining jurisdiction and profit allocation. The research method used is literature. The results show that tax reform in the digital era requires a multifaceted approach that includes policy reform, implementation of modern technology, and effective international coordination and cooperation. These results provide guidance for policymakers to create a more equitable, inclusive, and sustainable tax system in the face of the evolving dynamics of the digital industry.